Prosentase Investasi Dana Tabarru yang Dapat Diinvestasikan untuk mencegah Kekurangan Pembayaran Klaim Saat Defisit Underwriting - Wahyu - Waskito (Jurnal Jurisprudence, 2017)
The scientific article, discusses the fund of tabarru’ investment in Takaful. Issues raised is how many percentage the fund of tabarru investment on Takaful. The aim is to analyze and understand the concept of funds tabarru invesment, Islamic insurance and fund position tabarru in Takaful. This article, the normative research method conceptual approach. the result is that Percentage of tabarru’ funds investment is not set by default by the DSN or MUI fatwa. The percentage is more directed at the policy and agreement among the participants of insurance with the company.